(untitled) (Fiep Bulletin - online, 2013)
With all the importance of physical activity for health, there are still few population-based studies on the subject or school adolescents in Brazil. Among the surveys, the results show very high prevalence of physically inactive adolescents and strong association with demographic, socioeconomic and biologics9. The aim of this study was to encourage and educate 3623 students from 1st to 9th year of municipal and state schools in the city of Jacarezinho - PR to improve their lifestyle habits such as exercise, personal hygiene, nutrition and posture based on the application of an Physical Activity Questionnaire10 adapted and validated before and after a proposed program to encourage physical activity and lifestyle. Comparing the results from the 1st to the 2nd evaluation was found that 12% more children began to attend all physical education classes a week, 10% went by shoes to school, 2% started to brush their teeth after every meals and before meals 3% began to wash hands with soap and water. The children studied have low rates of physical activity, but improved their physical activity, hygiene and food after applying the program to encourage physical activity and lifestyle.